Fintech sebagai Determinan Green Marketing: Studi Literatur - Bhenu Artha; Antonius Satria Hadi; Bahri; Cahya Purnama Asri; Utami Tunjung Sari; Niken Permata Sari; Ascasaputra Aditya (Yayasan Literasi Emas Nusantara, 2026)
Introduction: The combination of financial technology (FinTech) and green marketing represents a transformative frontier in the pursuit of sustainable development. Along with the global challenges facing the world economy, such as climate change, resource scarcity, and shifting consumer values, both the financial and marketing sectors are undergoing rapid digitalization and a shift in orientation towards sustainability. Methods: This research uses theoretical review. Results: green marketing as a dependent variable influenced by fintech. Discussion: The integration of FinTech and green marketing raises important ethical questions regarding data privacy, consent, and algorithmic bias. While data-driven personalization can increase relevance and engagement, it also risks violating privacy and reinforcing inequality if not managed responsibly. Effective governance—which includes transparency, accountability, and stakeholder engagement—is essential for building and maintaining trust in FinTech-enabled green marketing. Collaboration between FinTech companies, traditional financial institutions, regulators, and civil society is crucial for developing robust standards, sharing best practices, and addressing systemic risks.